One-Step Regeneration of Hairy Roots to Induce High Tanshinone Plants in Salvia miltiorrhiza - Su, Yuekai; Lin, Caicai; Zhang, Jin; Hu, Bei; Wang, Jie; Li, Jingyu; Wang, Shiqi; Liu, Ruihao; Li, Xia; Song, Zhenqiao; Wang, Jianhua (Frontiers in Plant Science, 2022)
Salvia miltiorrhiza is a traditional Chinese medicinal plant of Labiatae, which has been widely utilized to treat a variety of cardiovascular and cerebrovascular diseases. Therefore, it is critical to use biotechnology to genetically modify S. miltiorrhiza in order to boost the content of beneficial components such as tanshinone IIA. In the present study, by inducing the production of root buds, we have developed a novel one-step regeneration method for hairy roots that can directly obtain regenerated plants and hairy roots with high tanshinone content. When the explants were infected with Ar.qual (OD600 = 0.6) for 10 minutes, co-cultured for 3 days, and then screened on the screening medium containing 7.5 mg/L hygromycin, the maximum positive frequency was 73.85%. GFP and PCR detection yielded a total of 9 positive hairy root lines and 11 positive regenerated plants. SmGGPPS1 was successfully overexpressed in positive regenerated plants, according to the results of qRT-PCR. The content of tanshinone IIA and cryptotanshinone were also dramatically enhanced in transgenic regenerated plants and hairy roots by UPLC analysis. Based on the Agrobacterium-mediated transformation of S. miltiorrhiza, this study developed a new method for regenerating plants with transgenic hairy roots. This method provides a foundation for the breeding of S. miltiorrhiza and the sustainable development of medicinal plant resources, as well as provides a useful reference for the application of other species.